Language personality and Edward Hall’s intercultural communication models (based on Mexican variety of Spanish language) - I. V. Guseva (Ибероамериканские тетради, 2015)
The article touches upon the problem of the correlation between the peculiarities of the national character and culture, the type of personality and their reflection in the language. It is explained why the process of mutual understanding is almost impossible without in-depth studies of the types of the cultures of language communities.